Pengujian Kebulatan Hasil Pembuatan Poros Aluminium Menggunakan Emco T.U CNC - 2A Smkn 2 Pekanbaru Dengan Roundness Tester Machine - Erizal Hamdi; Dodi Sofyan Arief; Adhy Prayitno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Lathing process is one of the main processes in the manufacturing industry. In the process of turning a product at TU EMCO CNC machine -2a SMKN2 Pekanbaru possible deviations from predetermined geometric characteristics. Aluminium is a light metal having corrosion resistance and good electrical conductivity. In the process of making a product (workpiece) is meticulous, the deviation of the shape, position, place, and rotate deviation to wardsan element geometry (point, line, surface or intermediate area), should be clearly limited to the value of a certain tolerance. Tolerance limits the form of deviation, position and place on aswivel deviation geometric element is referred to as geometric tolerances. Roundness and diameter are the two different geometric character, though interrelated, the lack roundness will affect the measurement results diameter, other wise the measurement of the diameter is not always going to show lack non roundness. From the results, the value of the roundness deviation of each variation of the feeding speed on the machine for the Minimum circumscribed circle feeding speed difference deviation 20 is between 0,011mm to 0,115 mm. feeding speed 40 is between 0.023 mm to 0.063 mm.feeding speed 70 is between 0.040 mm to 0.144 mm. On the Maximum incribed circle speed difference deviation 20 is between 0,007 mm to 0,100 mm. feeding speed 40 is between 0.025 mm to 0.059 mm. feeding speed 70 is between 0.010 mm to 0.108. In the Minimum zone circle feeding speed difference deviation 20 is between 0.011 to 0.109 mm. feeding speed 40 is between 0,024 mm to 0,076 mm. feeding speed 70 is between 0.044 mm to 0.092 mm. At Least Squares Circle feeding speed difference deviation 20 is between 0.008 to 0.029, feeding speed 40 is between 0.005 mm to 0.053 mm. 70 feeding speed is between 0,021mm to 0,047 mm.Roundness deviation value and average Least squares circle every variation of feeding speed, then at a feeding speed of 20 near-perfect roundness deviation value after deducting the correction factor Roundness Tester Machine tools, namely between -0.017 mm to 0,023 mm and the average value of 0.0037 mm.Keywords: feeding speed, Deviation, Roundness Tester Machine.